Out-of-pocket expenditures for pharmaceuticals: Lessons from the Austrian household budget survey - Alice Sanwald; Engelbert Theurl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
BACKGROUND: Paying pharmaceuticals out-of-pocket is an important source of financing pharmaceutical consumption. Only limited empirical knowledge is available on the determinants of these expenditures. OBJECTIVES: In this paper we analyze which characteristics of private households influence out-of-pocket pharmaceutical expenditure (OOPPE) in Austria. DESIGN & METHODS: We use cross-sectional information on OOPPE and on household characteristics provided by the Austrian household budget survey 2009/10. We split pharmaceutical expenditures into the two components prescription fees and over-the-counter (OTC) expenditures. To adjust for the specific characteristics of the data we compare different econometric approaches: two-part model, hurdle model, generalized linear model, zero-inflated negative binomial regression model. FINDINGS: The finally selected econometric approaches give a quite consistent picture. The probability of expenditures of both types is strongly influenced by the household structure. It increases with age, doctoral visits and the presence of a female householder. The education level and income only increase the probability of OTC-pharmaceuticals. The level of OTC-expenditures remains widely unexplained while the household structure and age influences the expenditures for prescription fees. Insurance characteristics of private households either private or public play a minor role in explaining the expenditure levels in all specifications. This refers to a homogenous and comprehensive provision of pharmaceuticals in the public part of the Austrian health care system. CONCLUSIONS: The paper gives useful insights into the determinants of pharmaceutical expenditures of private households and supplements the previous research which focuses on the individual level.
Keywords: I1; 330; out-of-pocket pharmaceutical expenditures; consumer survey; two part model; generalized linear model; hurdle model; zero-inflated negative binomial model